PtNPs/PEDOT:PSS-Modified Microelectrode Arrays Reveal Electrophysiological Activities of Different Neurons in Medial Amygdala of Mice Under Innate Fear - Fan, Penghui; Song, Yilin; Lu, Botao; Wang, Yiding; Dai, Yuchuan; Xie, Jingyu; He, Enhui; Xu, Zhaojie; Yang, Gucheng; Mo, Fan; Liu, Juntao; Wang, Mixia; et al. (Frontiers in Neuroscience, 2022)
The medial amygdala (MA) plays an important role in the innate fear circuit. However, the electrophysiological mechanism of MA for processing innate fear needs to be further explored. In this study, we fabricated microelectrode arrays (MEAs) with detecting sites arranged to match the location and shape of MA in mice and detected the electrophysiology in freely behaving mice under 2-methyl-2-thiazoline (2MT)-induced fear. The detection performance of MEA is improved by modifying metal nanoparticles and conductive polymers (PtNPs/PEDOT:PSS). After modification, the impedance magnitude and phase of electrodes were decreased to 27.0 ± 2.3 kΩ and −12.30 ± 0.52°, respectively, leading to a signal-to-noise ratio of 10. Its electrochemical stability and mechanical stability were also verified by cyclic voltammetry (CV) sweeping and ultrasonic vibration. MEAs were then implanted into the MA of mice, and the electrophysiology and behavioral characteristics were synchronously recorded and analyzed. The results showed that 2MT induced strong defensive behaviors in mice, accompanied by increases in the average spike firing rate and local field potential (LFP) power of MA neurons. According to principles commonly applied to cortical extracellular recordings, the recorded neurons are divided into two classes based on waveforms. Statistics showed that about 37% of type 1 neurons (putative GABAergic neurons) and 87% of type 2 neurons (putative glutamatergic neurons) were significantly activated under innate fear. At the same time, the firing rate of some activated neurons had a good linear correlation with the freezing rate.